Posttraumatic Resorption of Permanent Teeth - H. Hecová; P. Fiala; P. Vais; V. Merglová (Czech Dental Chamber, 2006)
The root resorption belongs to the most severe consequence after the injury. The aim of our study was to analyze a group of 510 teeth with different types of dental injuries. In the group of our patients we found 39 teeth with external resorption and 10 teeth with internal resorption process. Eleven teeth had to be extracted after establishing advanced resorption of the root.